Edge-interior differences in the species richness and abundance of drosophilids in a semideciduous forest fragment - Penariol, Leiza V. [UNESP] (2013)
Habitat fragmentation is the main cause of biodiversity loss, as remnant fragments are exposed to negative influences that include edge effects, prevention of migration, declines in effective population sizes, loss of genetic variability and invasion of exotic species. The Drosophilidae (Diptera), especially species of the genus Drosophila, which are highly sensitive to environmental variation, have been used as bioindicators. A twelve-month field study was conducted to evaluate the abundance and richness of drosophilids in an edge-interior transect in a fragment of semideciduous forest in São Paulo State, Brazil. One objective of the study was to evaluate the applied methodology with respect to its potential use in future studies addressing the monitoring and conservation of threatened areas. The species abundance along the transect showed a clear gradient, with species associated with disturbed environments, such as Drosophila simulans, Scaptodrosophila latifasciaeformis and Zaprionus indianus, being collected at the fragment edge and the species D. willistoni and D. mediostriata being found in the fragment's interior. Replacement of these species occurred at approximately 60 meters from the edge, which may be a reflection of edge effects on species abundance and richness because the species found within the habitat fragment are more sensitive to variations in temperature and humidity than those sampled near the edge. The results support the use of this methodology in studies on environmental impacts. © 2013 Penariol and Madi-Ravazzi; licensee Springer.